Površinsko širjenje zmrzlin - Jaksetič, Kevin (Matrika, 2022)
Frost formation depends on the type of surface and its temperature, but also on humidity and temperature of the atmosphere. A dense enough distribution of water droplets that form on the surface can lead to “chain reactions”. We get this kind of regime by having a very humid atmosphere surrounding the surface. This way, frost spreading is faster than in a dry atmosphere where the spreading happens only due to the diffusion of water vapor from the surrounding gas. At certain conditions, at medium atmosphere humidity, the spreading happens in an intermediate mode, in which the chain reactions are limited.
Keywords: frost; slana; spreading; širjenje zmrzlin; termodinamika; thermodynamics; zmrzovanje